Ghrelin: A Potent Nephro-protective Agent against Nicotine Induced Kidney Damage in Mice - Aqsa Jabeen, Sadia Ahsin, Nasar Abbas, Zara Shaukat, Hira Kiyani (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Kidneys are the major organs responsible for elimination of toxic metabolites from the body. Apart from this kidneys play a vital role in maintaining body fluid and electrolyte balance, blood pressure regulation, red blood cells production and vitamin D activation. Aim: To evaluate role of ghrelin in ameliorating nicotine induced kidney damage by estimating renal function test and serum antioxidant enzymes in BALB/c mice. Methodology: It was a Randomized Control Trial. Healthy male BALB/c mice (n=27) were taken from NIH Islamabad and sorted into 3 groups (nine each). Group I was labeled as control group and given intra-peritoneal normal saline for 29 days. Group II was labeled as nicotine group and received intra-peritoneal nicotine for 29 days. Group III was labeled as ghrelin + nicotine and received intra-peritoneal ghrelin on alternate days and nicotine daily for 29 days. On 30th day intra-cardiac sampling was done for estimation of renal function test and serum antioxidant enzyme levels. Data was evaluated by using SPSS version 23. One way ANOVA and post hoc tukey’s test were applied. Results: In group II, nicotine administration led to decrease level of antioxidants enzymes and significant deterioration of renal function test in comparison with group I. In group III, administration of ghrelin along with nicotine prevented the fall in antioxidant enzymes and restored renal function test back to normal. Practical Implication: Ghrelin a newly discovered peptide has shown to have anti-oxidant properties and thus has potential to reduce the onset and progression of different diseases. It can directly remove reactive oxygen species or can increase the levels of anti-oxidant enzymes thus nullifying oxidative damage. Conclusion: It was concluded that ghrelin by virtue of its anti-oxidant properties protects against nicotine induced kidney damage as reflected through restoration of serum antioxidant enzymes and renal function test. Keywords: Ghrelin, Oxidative Stress, Nicotine, Anti-oxidant Enzymes.